2022
DOI: 10.1371/journal.pone.0262141
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status of informal waste workers during the COVID-19 pandemic in Bangladesh

Abstract: The deadliest coronavirus disease 2019 (COVID-19) is taking thousands of lives worldwide and presents an extraordinary challenge to mental resilience. This study assesses mental health status during the COVID-19 pandemic and its associated factors among informal waste workers in Bangladesh. A cross-sectional survey was conducted in June 2020 among 176 informal waste workers selected from nine municipalities and one city corporation in Bangladesh. General Health Questionnaire (GHQ-12) was used to assess respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 58 publications
(79 reference statements)
3
17
0
1
Order By: Relevance
“…The main results found in the present systematic review are in line with studies in the general population that have shown the frequent use of antidepressants around the world, a fact that may be due to the increase in mental disorders (MD) that are currently configured as an important public health problem (Santos et al, 2019). As for the profile of affected individuals, a survey showed that women are more likely to develop MD, which may be associated with greater exposure and use of antidepressants, including during pregnancy (Haque et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…The main results found in the present systematic review are in line with studies in the general population that have shown the frequent use of antidepressants around the world, a fact that may be due to the increase in mental disorders (MD) that are currently configured as an important public health problem (Santos et al, 2019). As for the profile of affected individuals, a survey showed that women are more likely to develop MD, which may be associated with greater exposure and use of antidepressants, including during pregnancy (Haque et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…The less people dependent on homemade food, the higher they are suffering from severe anxiety. This goes with the results of a study that was performed on informal workers during the COVID-19 pandemic in Bangladesh [ 25 ]. Unhealthy food, soft drinks, and fast food were found to be associated with significant stress, depressive symptoms, and sleep disturbance [ 26 ].…”
Section: Discussionsupporting
confidence: 82%
“…The impacts, however, varied with the urban-rural nature, gender, locations, level of education, types of work, and age of the informal sector workers in Bangladesh. The absence of official protection and recognition, social security system, and restricted benefits from institutional sources has pushed informal sector workers to a precarious condition [ 8 , 12 , 60 ]. Another finding of this study was that the pandemic had less impact on the income of the rural informal workers, especially those who were involved in agriculture-based employment.…”
Section: Discussionmentioning
confidence: 99%